Clomiphene-Metformin vs Clomiphene in Infertil Women with Polycystic Ovary Syndrome: A Systematic Review and Meta-analysis - Prilia, Arifah Mabruroh; Kurniawati, Devita; Pramono, Adi; Jiwanggana, Parada (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Objective: To compare the efficacy of clomiphene citrate and metformin with clomiphene citrate alone in treating primary infertility in women with polycystic ovarian syndrome.Methods: PubMed, SCOPUS, and Google Scholar databases were searched for English-language randomized controlled trials from 2015 to 2024. Inclusion criteria: reproductive age group (15 - 35 years), all ethnicities, diagnosed with PCOS by all current criteria, who are primarily infertile, and received clomiphene citrate and metformin compared to clomiphene citrate alone or with placebo. Primary outcomes: efficacy or improvement in fertility.Result: The search returned 1251 articles; 120 articles addressed metformin or clomiphene citrate, and four randomized controlled trials (RCTs) comparing metformin and clomiphene citrate with clomiphene citrate alone were included. One thousand seven hundred thirty-seven (1737) women with primary infertility and PCOS were included in this systematic review. The dose of metformin was 500 - 850mg twice or thrice daily, and the dose of clomiphene citrate was 50 - 100mg once daily. Based on four articles, the efficacy of fertility improvement of metformin and clomiphene citrate was significantly higher (231/869; 26.58%) compared to clomiphene citrate alone or with placebo (169/868; 19.47%) (OR = 1.5; 95% CI 1.10 [1.04-1.15]; p-value = 0.0004, 4 trials; I2 = 49%; n = 1737).Conclusion: Metformin and clomiphene citrate are more effective for improving fertility than clomiphene alone or placebo, respectively. Further methodological trials are necessary to identify additional differences in effectiveness and other outcomes between metformin and clomiphene citrate, particularly regarding safety and adverse effects.Clomifene-Metformin vs Clomifene pada Wanita Infertil Primer dengan Sindrom Ovarium Polikistik: Systematic Review dan Meta-AnalysisAbstrakTujuan: Penelitian ini dilakukan untuk membandingkan efikasi clomifene sitrat dan metformin versus clomifene sitrat pada terapi infertilitas primer pada wanita dengan sindrom ovarium polikistik.Metode: Pencarian menggunakan database Pubmed, SCOPUS, dan Google Scholar untuk Randomized Controlled Trials berbahasa Inggris dari tahun 2015 sampai 2024. Kriteria inklusi: kelompok usia produktif (15 - 35 tahun), semua etnis, didiagnosis dengan PCOS dengan seluruh kriteria, merupakan pasien infertil primer, mendapatkan clomifene sitrat dan metformin dibandingkan dengan clomifen sitrat saja atau dengan plasebo. Hasil primer: efikasi peningkatan fertilitas,Hasil: Hasil pencarian adalah 1251 artikel; 120 artikel membahas metformin atau clomifene sitrat, dan empat RCT yang dilakukan systematic review dan meta-analysis. Seribu tujuh ratus tiga puluh tujuh (1737) wanita infertil primer dan PCOS masuk ke dalam systematic review ini. Dosis metformin adalah 500 - 850mg dua atau tiga kali sehari, dan dosis clomifene sitrat adalah 50 - 100mg sekali sehari. Berdasarkan empat artikel, efikasi peningkatan fertilitas dari metformin dan clomifene sitrat signifikan lebih tinggi (231/869; 26.58%) dibandingkan dengan clomifene sitrat saja atau dengan plasebo (169/868; 19.47%) (OR = 1.5; 95% CI 1.10 [1.04-1.15]; p-value = 0.0004, 4 trials; I2 = 49%; n = 1737).Kesimpulan: Metformin dan clomifene sitrat memiliki efikasi peningkatan fertilitas yang lebih baik dibandingkan dengan clomifene sitrat saja atau dengan plasebo. Uji metodologi lebih lanjut dibutuhkan untuk menentukan perbedaan lebih lanjut dari keefektifan dan hasil lainnya antara metformin dan clomifene sitrat, dengan mempertimbangkan keamanan dan efek samping.